PENGELOLAAN MODAL KERJA - Lidwina Monica (Center for Economic Studies Universitas Katolik Parahyangan, 1999)
Working Capital is an important factor in every company. People who want to start a business might prepare sales, production, marketing and profit planning very prudent, but they often ignore the importance of managing the working capital. Therefore, many profitable companies go bankrupt because of working capital mismanagement. Understanding concepts and the sources of working capital will help managers to run their business.